Comprehensive metagenomic analysis of glioblastoma reveals absence of known virus despite antiviral‐like type I interferon gene response - Cosset, Érika; Petty, Tom J.; Dutoit, Valérie; Cordey, Samuel; Padioleau, Ismael; Otten‐Hernandez, Patricia; Farinelli, Laurent; Kaiser, Laurent; Bruyère‐Cerdan, Pascale; Tirefort, Diderik; Amar El‐Dusouqui, Soraya; Nayernia, Zeynab; et al. (International journal of cancer, 2014)
Glioblastoma is a deadly malignant brain tumor and one of the most incurable forms of cancer in need of new therapeutic targets. As some cancers are known to be caused by a virus, the discovery of viruses could open the possibility to treat, and perhaps prevent, such a disease. Although an association with viruses such as cytomegalovirus or Simian virus 40 has been strongly suggested, involvement of these and other viruses in the initiation and/or propagation of glioblastoma remains vague, controversial and warrants elucidation. To exhaustively address the association of virus and glioblastoma, we developed and validated a robust metagenomic approach to analyze patient biopsies via high‐throughput sequencing, a sensitive tool for virus screening. In addition to traditional clinical diagnostics, glioblastoma biopsies were deep‐sequenced and analyzed with a multistage computational pipeline to identify known or potentially discover unknown viruses. In contrast to the studies reporting the presence of viral signatures in glioblastoma, no common or recurring active viruses were detected, despite finding an antiviral‐like type I interferon response in some specimens. Our findings highlight a discrete and non‐specific viral signature and uncharacterized short RNA sequences in glioblastoma. This study provides new insights into glioblastoma pathogenesis and defines a general methodology that can be used for high‐resolution virus screening and discovery in human cancers. What's new? Glioblastoma remains frustratingly difficult to cure. There is some evidence to suggest viruses might contribute to glioblastoma, a very tempting possibility, as the involvement of a virus could open doors to formulating novel treatments. However, the role of viruses is still vague and controversial. In this study the authors have developed a robust megagenomic approach to search tumor tissue for the presence of viruses, the first of its kind. They found no common or recurring active viruses, although they did detect a non‐specific interferon pattern resembling an antiviral response.